2019
DOI: 10.1021/acssynbio.9b00169
|View full text |Cite
|
Sign up to set email alerts
|

Industrializing a Bacterial Strain for l-Serine Production through Translation Initiation Optimization

Abstract: Supplementary Figure S1. Development and validation of a medium throughput HPLC method for the detection of L-serine in microbial culture supernatant. (a) Overlaid HPLC chromatogram of L-serine standards. (b) The recovery of L-serine from spiked samples (n=5). (c) Reproducability of the method (n=5) for different L-serine concentrations. (d) Calibration curve for L-serine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
(111 reference statements)
0
15
3
Order By: Relevance
“…However, Lserine titer did not significantly change when serAΔ197 and serC were respectively overexpressed in A36 (with L-serine titer of 31.1 and 32.78 g/L, respectively). In a recent study, 50 g/L L-serine was produced with glucose as the carbon source in E. coli, which is the highest L-serine production reported so far; however, the yield was 0.36 g/g glucose [36], which is lower than that obtained in the present study (0.44 g/g sucrose). Therefore, fine controlling of the three enzymes of L-serine biosynthesis pathway could possibly further enhance L-serine production.…”
Section: Discussioncontrasting
confidence: 85%
“…However, Lserine titer did not significantly change when serAΔ197 and serC were respectively overexpressed in A36 (with L-serine titer of 31.1 and 32.78 g/L, respectively). In a recent study, 50 g/L L-serine was produced with glucose as the carbon source in E. coli, which is the highest L-serine production reported so far; however, the yield was 0.36 g/g glucose [36], which is lower than that obtained in the present study (0.44 g/g sucrose). Therefore, fine controlling of the three enzymes of L-serine biosynthesis pathway could possibly further enhance L-serine production.…”
Section: Discussioncontrasting
confidence: 85%
“…Interestingly, we found that L-serine titer increased significantly by overexpressing serB in A36, with L-serine titer of 37.9 g/L, which was 24% higher than that of A36, serB encoded phosphoserine phosphatase (PSP, EC 3.1.3.3), catalyzed the last step of Lserine biosynthesis, however, L-serine titer had not significantly change when serAΔ197, serC was overexpressed in A36 respectively (with L-serine titer of 31.1 g/L and 32.78 g/L) (Fig.S5), and these results were in consistent with the previous report completely, in which overexpression of the mutant allele serAΔ197 in C. glutamicum13032 either alone or in combination with overexpression of serC and serB did not result in significant L-serine accumulation [3],which might be due to the poor accumulation and intracellular conversion of L-serine in C. glutamicum13032. In a recent study, 50 g/L of L-serine was produced with glucose as carbon source in E. coli, with a yield of 0.26-0.30 g/g glucose [37], in which 50 g/L is the highest reported so far for L-serine production, however, the yield was also lower than our present study (0.44 g/g sucrose). It is possible that fine controlling the three enzymes of the L-serine biosynthesis pathway to enhance L-serine production further.…”
contrasting
confidence: 76%
“…OD and serine were measured continuously for 24 hr. At the end of cultivation, serine titers reached 0.55 g/L (Figure 5a), slightly lower than the 0.62 g/L achieved when using lac‐T7 (Rennig et al, 2019). A decrease in growth rate and final OD could be seen for the serine‐producing strain, which may be due to carbon being utilized for serine production instead of growth.…”
Section: Resultsmentioning
confidence: 62%
“…We chose to only apply one of the cassettes, as mCherry production levels of trp‐T7 and trp*‐T7 were similar according to flow cytometry (Figure 3b). The strain was transformed with pSEVA27‐sl‐ serA mut CB TIR1 (hereafter pSEVA‐serACB) harboring an expression‐optimized serine operon under control of pT7 (Rennig et al, 2019), resulting in strain trp‐T7‐ser.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation